Influence of Ca concentration on the electric, morphological, and structural properties of (Pb,Ca)TiO3 thin films - Pontes, F. M.; Pontes, DSL; Leite, E. R.; Longo, Elson [UNESP]; Santos, EMS; Mergulhao, S.; Chiquito, A.; Pizani, P. S.; Lanciotti, F.; Boschi, T. M.; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2002)
Pb1-xCaxTiO3 (0.10less than or equal toxless than or equal to0.40) thin films on Pt/Ti/SiO2/Si(100) substrates were prepared by the soft solution process and their characteristics were investigated as a function of the calcium content (x). The structural modifications in the films were studied using x-ray diffraction and micro-Raman scattering techniques. Lattice parameters calculated from x-ray data indicate a decrease in lattice tetragonality with the increasing content of calcium in these films. Raman spectra exhibited characteristic features of pure PbTiO3 thin films. Variations in the phonon mode wave numbers, especially those of lower wave numbers, of Pb1-xCaxTiO3 thin films as a function of the composition corroborate the decrease in tetragonality caused by the calcium doping. As the Ca content (x) increases from 0.10 to 0.40, the dielectric constant at room temperature abnormally increased at 1 kHz from 148 to 430. Also calcium substitution decreased the remanent polarization and coercive field from 28.0 to 5.3 muC/cm(2) and 124 to 58 kV/cm, respectively. These properties can be explained in terms of variations of phase transition (ferroelectric-paraelectric), resulting from the substitution the lead site of PbTiO(3)for the nonvolatile calcium. (C) 2002 American Institute of Physics.